Pdx1 and BETA2/NeuroD1 Participate in a Transcriptional Complex That Mediates Short-range DNA Looping at the Insulin Gene - Babu, Daniella A. (American Society for Biochemistry and Molecular Biology, 2008)
The activity of the insulin gene, Ins, in islet β cells is thought to arise in part from the synergistic action of the transcription factors Pdx1 and BETA2/NeuroD1. We asked how the binding of these factors to A and E elements many tens or hundreds of base pairs upstream of the start site could influence activity of transcriptional machinery. We therefore tested the hypothesis that the complex of Pdx1 and BETA2/NeuroD1 maintains a DNA conformation such that distal regions of the gene are brought into proximity of the promoter and coding region. We show by coimmunoprecipitation that Pdx1 and BETA2/NeuroD1 exist within a complex and that the two physically interact with one another in this complex as assessed by fluorescence resonance energy transfer. Consistent with this interaction, we found that the two factors simultaneously occupy the same fragment of the Ins gene in β cell lines using the chromatin immunoprecipitation/re-chromatin immunoprecipitation assay. Using a modification of the chromosome conformation capture assay in vitro and in β cells, we observed that Pdx1 and BETA2/NeuroD1 mediate looping of a segment of Ins that brings EcoRI sites located at –623 and +761 bp (relative to the transcriptional start site) in proximity to one another. This looping appears to be dependent in vitro upon an intact A3 binding element, but not upon the E2 element. Based on our findings, we propose a model whereby Pdx1 and BETA2/NeuroD1 physically interact to form a nucleoprotein complex on the Ins gene that mediates formation of a short DNA loop. Our results suggest that such short loop conformations may be a general mechanism to permit interactions between transcription factors and basal transcriptional machinery.